Ratio Decidendi Terhadap Amar Putusan Pengadilan Tata Usaha Negara pada Perkara Pemberhentian Tidak Dengan Hormat Aparatur Sipil Negara Terpidana Korupsi - Himawan, Mohammad Hilmi; Alfons, Saartje Sarah; Nendissa, Renny Heronia (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introductioan: The ratio decidendi or the judge's legal considerations is the most important thing in determining the decision because there are aspects that must be considered. Ratio decidendi is a process that will produce a decision. In practice, namely at the State Administrative Court, it was found the fact that the employment dispute, namely dishonorable dismissal, had a different decision. Purposes of the Research: This study aims to determine the ratio decidendi that produces different decisions. The purpose of this research will be to answer the anxiety and curiosity about the ratio decidendi of the dispute regarding the dishonorable dismissal. Methods of the Research: This writing method is normative juridical, with the type of library research, which uses a law approach, with the hope of answering the problems faced. Results of the Research: The difference in the decision of course must be drawn on the ratio decidendi which considers the authority to adjudicate, procedural and substantive aspects as well as aspects of the grace period. These three aspects will be the main focus in dissecting the ratio decidendi in each decision so that differences will be found. The consistency of the ratio decidendi can affect the legal certainty received by the parties.